2015
DOI: 10.1007/s11356-015-4179-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant-assisted rhizoremediation of decabromodiphenyl ether for e-waste recycling area soil of Taizhou, China

Abstract: To develop an effective phytoremediation approach to purify soils polluted by decabromodiphenyl ether (BDE-209) in e-waste recycling area, pot experiments were conducted through greenhouse growth of seven plant species in BDE-209-polluted soils. The hygrocolous rice (Oryza sativa L.) cultivars (XiuS and HuangHZ) and the xerophyte ryegrass (Lolium perenne L.) were found to be as the most effective functional plants for facilitating BDE-209 dissipation, with the removal of 52.9, 41.9, and 38.7% in field-contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…In typical E-waste dismantling area, polybrominated diphenyl ethers (PBDEs), used as flame retardants in electronic components, have drawn great public attention. Their environmental release during non-standard dismantling of E-waste has caused serious contamination in Taizhou and Guiyu of China, two of the largest E-waste dismantling sites in the world (He et al, 2015). Previous pollution surveys reported that the total concentration of PBDEs reached to greater than 3000 µg$kg -1 which caused serious environmental damage and food security risk (Qu et al, 2007;Zhao et al, 2010;Wang et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In typical E-waste dismantling area, polybrominated diphenyl ethers (PBDEs), used as flame retardants in electronic components, have drawn great public attention. Their environmental release during non-standard dismantling of E-waste has caused serious contamination in Taizhou and Guiyu of China, two of the largest E-waste dismantling sites in the world (He et al, 2015). Previous pollution surveys reported that the total concentration of PBDEs reached to greater than 3000 µg$kg -1 which caused serious environmental damage and food security risk (Qu et al, 2007;Zhao et al, 2010;Wang et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, facilitating environmental removal of PBDEs from polluted soils is crucial for pollution control and remediation in these Ewaste dismantling areas (Deng et al, 2016). Of all the 209 kinds PBDE congeners, the highest brominated decabromodiphenyl ether (BDE-209) owns the highest amount in total production of PBDEs because of its lower price and superior performance (Sjödin et al, 1999;He et al, 2015). There is thus an urgent need to mitigate the heavy pollution of BDE-209.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological activity, especially root exudation, has been demonstrated to significantly affect the behaviors of organic contaminants in soils (Luo et al 2006;Zhu et al 2009;Balseiro-Romero et al 2014;Martin et al 2014;He et al 2015). Some studies have evidenced the effects of root exudates on the desorption and availability of organic contaminants in soils.…”
Section: Introductionmentioning
confidence: 99%
“…The plant species basically uptake, store or degrade the pollutants. Numerous plant species have been successfully applied for restoration of sites contaminated with diverse pollutants arising from e-waste 19 . Chen et al 20 have tested the efficiency of four plant species, Medicago sativa (alfalfa), Lolium perenne (rye grass), Festuca arundinacea (tall fescue), and Oryza sativa (rice) for phytoremediation of PCB-contaminated soil from an e-waste disposal site.…”
Section: Phytoremediationmentioning
confidence: 99%